Synthesis and Characterization of Ni(II), Cu(II) and Co(II) Complexes with Bidentate Schiff Base Ligand Derived from 2,3,4,5-Tetrahydro indeno[1,2- d]thiazolo[3,2-a][1,3]pyrimidine-11(H)-one - Rai, B.K.; Kumar, Bimal (Asian Journal of Chemistry, 2011)
The present work reports the synthesis of a series of Co(II), Ni(II) and Cu(II) complexes of neutral bidentate Schiff base prepared by the condensation of 2,3,4,5-tetrahydro indeno[1,2-d]thiazolo[3,2-a][1,3]pyrimidine-11(H)-one with semicarbazide hydrochloride. The ligand as well as metal complexes have been characterized by elemental analyses, molar mass, magnetic susceptibility, molecular conductivity, IR spectra, electronic spectra. On the basis of above observations, it is proposed that the ligand 2,3,4,5-tetrahydro indeno[1,2-d]thiazol[3,2- a][1,3]pyrimidine-11(H)-semicarbazone behaves as neutral bidentate manner and coordination takes place through azomethine N and carbonyl oxygen of semicarbazone moiety. The remaining positions of the metal ion are satisfied by negative ions such as Cl–, Br–, I– and NO3 –. The complexes were proposed octahedral geometry.